LEVERAGING WHATSAPP GROUP AS A LEARNING DEVICE TO ENHANCE STUDENTS’ SPEAKING SKILLS - Nengah Dwi Handayani; Ida Ayu Made Sri Widiastuti; Ida Bagus Nyoman Mantra (Unmas Press, 2021)
The improvement of speaking skills is highly important to be intensified to continually develop students’ speaking skills. Speaking skills need special attention because a good speaking skill cannot be obtained automatically without appropriate learning activities and intensive practice. Language skills, especially speaking skills, can affect students' communication skills, therefore the efforts to improve students’ speaking skills become a priority in English language learning. This study was conducted on university students with the aim of developing their speaking skills through the WhatsApp group application. The study showed that the students’ speaking skills improved considerably high after the integration of WhatsApp group intro English language learning. Therefore, the study implies that the WhatsApp group can be utilized by the language teachers to improve their students speaking skills.